Endurance training enhances skeletal muscle interleukin-15 in human male subjects - Rinnov, Anders; Yfanti, Christina; Nielsen, Søren; Åkerström, Thorbjörn C. A.; Peijs, Lone; Zankari, Alaa; Fischer, Christian P.; Pedersen, Bente K. (Endocrine, 2014)
Regular endurance exercise promotes metabolic and oxidative changes in skeletal muscle. Overexpression of interleukin-15 (IL-15) in mice exerts similar metabolic changes in muscle as seen with endurance exercise. Muscular IL-15 production has been shown to increase in mice after weeks of regular endurance running. With the present study we aimed to determine if muscular IL-15 production would increase in human male subjects following 12 weeks of endurance training. In two different studies we obtained plasma and muscle biopsies from young healthy subjects performing: (1) 12 weeks of ergometer cycling exercise five times per week with plasma and biopsies before and after the intervention, and (2) 3 h of ergometer cycling exercise with plasma and biopsies before and after the exercise bout and well into recovery. We measured changes in plasma IL-15, muscle IL-15 mRNA and IL-15 protein. Twelve weeks of regular endurance training induced a 40 % increase in basal skeletal muscle IL-15 protein content ( p < 0.01), but with no changes in either muscle IL-15 mRNA or plasma IL-15 levels. However, an acute bout of 3-h exercise did not show significant changes in muscle IL-15 or plasma IL-15 levels. The induction of muscle IL-15 protein in humans following a regular training period supports previous findings in mice and emphasizes the hypothesis of IL-15 taking part in skeletal muscle adaptation during training.